Inhibitors of Post-Translational Modifications of G-Proteins as Probes to Study the Pancreatic β Cell Function: Potential Therapeutic Implications - Kowluru, A.; Amin, R. (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2002)
It is well established that glucose-induced insulin secretion involves generation of intracellular second messengers. Using specific inhibitors of guanosine triphosphate [GTP] biosynthesis [e.g., mycophenolic acid MPA], we have identified a permissive role for GTP in glucose-stimulated insulin secretion. While the exact site of action for GTP within the islet β cell remains to be identified and defined, recent evidence from several laboratories, including our own, indicate that it could involve activation of GTPbinding proteins [G-proteins]. These studies have identified both trimeric and monomeric forms of G-proteins within the pancreatic β cell. Recent data also indicate that these G-proteins, specifically the monomeric Gproteins and the γ subunits of trimeric G-proteins undergo a series of posttranslational modifications at their C-terminal cysteine. Such modifications include, isoprenylation, carboxyl methylation and palmitoylation. These modification steps appear to be essential for translocation of these proteins to the membrane sites for interaction with their respective effector proteins. This review primarily focuses on recent findings that clearly support the viewpoint that these posttranslational modification steps not only play obligatory roles in fuel-induced insulin secretion, but also in cytokine-mediated apoptotic demise of the β cell. In this review, we also attempted to describe those findings involving the use of specific inhibitors for each of these pathways, and it is our hope that these aspects of β cell metabolism and function generate interest in development of therapeutic intervention modalities to states of perturbed insulin release.
Keywords: gtp inhibitor